Morphometric parameters of the optic disc in normal and glaucomatous eyes based on time-domain optical coherence tomography image analysis - Dovilė Buteikienė; Asta Kybartaitė-Žilienė; Loresa Kriaučiūnienė; Valerijus Barzdžiukas; Ingrida Janulevičienė; Alvydas Paunksnis (Medicina, 2017)
Background and objective: Assessment of optic disc morphology is essential in diagnosis and management of visual impairment. The aim of this study was to evaluate associations between optic disc morphometric parameters, i.e., size and shape, and age, gender, and ocular axial length in normal and glaucomatous eyes based on time-domain optical coherence tomography image analysis.Materials and methods: It was a case–control study of 998 normal and 394 eyes with primary open angle glaucoma that underwent an ophthalmological examination and time-domain optical coherence topography scanning. Areas and shapes of the disc, cup, and neuroretinal rim were analyzed.Results: The shape of the optic disc did not differ between the study groups, i.e., normal and glaucomatous case groups, but the disc area of the primary open angle glaucoma group was significantly larger. The shape of the small disc was significantly different, but the shape of the medium and the large disc did not differ between the study groups. The central area of the disc, i.e., cup area was significantly larger in the case group and its shape was significantly different between the study groups. No significant differences in the area of the cup and its shape, nerve fibers on the edge of the disc, i.e., neuroretinal rim area, were found between the study groups of the small discs. There were significant associations between age, gender, and ocular axial length and morphometric parameters of the optic disc.Conclusions: Informative results with regard to the size and shape due to various ocular characteristics between the healthy control group and patients suffering with primary open angle glaucoma were obtained. Both study groups were significant in size, which makes the findings interesting and important contribution in the field.